2001
DOI: 10.1074/jbc.m008234200
|View full text |Cite
|
Sign up to set email alerts
|

The Dynamics of Myogenin Site-specific Demethylation Is Strongly Correlated with Its Expression and with Muscle Differentiation

Abstract: The molecular mechanisms underlying the activation of tissue-specific genes have not yet been fully clarified. We analyzed the methylation status of specific CCGG sites in the 5-flanking region and exon 1 of myogenin gene, a very important myogenic differentiation factor. We demonstrated a loss of methylation, at the onset of C2C12 muscle cell line differentiation, limited to the CCGG site of myogenin 5-flanking region, which was strongly correlated with the transcriptional activation of this gene and with myo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
98
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 122 publications
(104 citation statements)
references
References 73 publications
5
98
1
Order By: Relevance
“…S-Adenosyl methionine has been used previously to induce methylation of myogenic genes in myoblasts. (30,31) Similar results were obtained using a small interfering RNA to knock down SM22a expression. A discrete fall in mRNA expression of SM22a (similar to that observed with phosphate treatment) was enough to enhance of Cbfa1 expression in shortterm cultures.…”
Section: Discussionsupporting
confidence: 57%
“…S-Adenosyl methionine has been used previously to induce methylation of myogenic genes in myoblasts. (30,31) Similar results were obtained using a small interfering RNA to knock down SM22a expression. A discrete fall in mRNA expression of SM22a (similar to that observed with phosphate treatment) was enough to enhance of Cbfa1 expression in shortterm cultures.…”
Section: Discussionsupporting
confidence: 57%
“…Since the 51-kb region between Myog and its upstream gene lacks CpG islands, DNA methylation in the vicinity of the promoter is probably responsible for Myog silencing. Consistent with this, Lucarelli et al reported that the methylation status of a single CCGG site at 340 bp upstream from the transcriptional start site (TSS) affects Myog transcription in mouse tissues and in C2C12, a skeletal muscle satellite-derived myoblast cell line [17]. This HpaII recognition site (CCGG), which is in the region proximal to the Myog promoter, was identified using the methylationsensitive endonuclease HpaII-PCR assay.…”
Section: Introductionmentioning
confidence: 73%
“…Treatment of 10T1/2 fibroblasts with the DNA demethylating reagent 5-aza-dC, or expression of antisense Dnmt1, results in myotube formation, suggesting that global demethylation plays a role in myogenic differentiation [14,15]. Similarly, 5-aza-dC treatment induces Myog expression in myoblast cells, implying that DNA methylation is also involved in the suppression of Myog transcription [16,17]. Since the 51-kb region between Myog and its upstream gene lacks CpG islands, DNA methylation in the vicinity of the promoter is probably responsible for Myog silencing.…”
Section: Introductionmentioning
confidence: 99%
“…Active demethylation was reported for genomic DNA upon induction of Epstein Barr virus lytic cycle [Szyf et al, 1985] for the myosin gene in differentiating myoblast cells [Lucarelli et al, 2001], for Il2 gene upon T cell activation [Bruniquel and Schwartz, 2003] and the INTERFERON GAMMA gene upon antigen exposure of memory CD8 T cells [Kersh et al, 2006]. However, if DNA methylation is plastic in mature postmitotic tissue and responsive to the environment throughout the life of an organism, mechanisms must exist to enable both introduction of new DNA methylation sites by de novo methylation and mechanisms for removal of DNA methylation by demethylation.…”
Section: Reversibility Of Dna Methylation In Somatic Tissuesmentioning
confidence: 99%